Maximizing opportunities by leveraging the strategic risk management within the scientific institute - Jonović Marija; Barjaktarović Lidija; Bugarin Dejan (Mining and Metallurgy Engineering Bor)
The research is based upon the insights derived from the conclusions of Jonović et al. (2024) and aims to evaluate the effectiveness of Strategic Risk Management (SRM) linked to the COSO ERM (Committee of Sponsoring Organizations Enterprise Risk Management) framework. Implemented within a scientific institute of significant importance to the Republic of Serbia, the SRM is examined for its ability to identify the weaknesses, address threats, and leverage opportunities. The goal is to identify the risk factors and mitigate them through the SRM as a concept closely related to the COSO ERM framework. The primary research includes a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis survey conducted from June 26 to July 1, 2024, with a sample of 214 respondents and a response rate of 55.6% (119 respondents). The results highlight a sustainable business strategy and effective application of the SRM in the institute.